Engineered In vitro Models for Pathological Calcification: Routes Toward Mechanistic Understanding. Issue 8 (3rd July 2021) - Radvar, Elham; Griffanti, Gabriele; Tsolaki, Elena; Bertazzo, Sergio; Nazhat, Showan N.; Addison, Owen; Mata, Alvaro; Shanahan, Catherine M.; Elsharkawy, Sherif
Abstract : Physiological calcification plays an essential part in the development of the skeleton and teeth; however, the occurrence of calcification in soft tissues such as the brain, heart, and kidneys associates with health impacts, creating a massive social and economic burden. The current paradigm for pathological calcification focuses on the biological factors responsible for bone‐like mineralization, including osteoblast‐like cells and proteins inducing nucleation and crystal growth. However, the exact mechanism responsible for calcification remains unknown. Toward this goal, this review dissects the current understanding of structure–function relationships and physico‐chemical properties of pathologic calcification from a materials science point of view. We will discuss a range of potential mechanisms of pathological calcification, with the purpose of identifying universal mechanistic pathways that occur across multiple organs/tissues at multiple length scales. The possible effect of extracellular components in signaling and templating mineralization, as well as the role of intrinsically disordered proteins in calcification, is reviewed. The state‐of‐the‐art in vitro models and strategies that can recreate the highly dynamic environment of calcification are identified. Abstract : Pathological calcification being a reason behind high mortality diseases including cardiovascular diseases, kidney stones, and Alzheimer's disease. However, lack of knowledge about its mechanism acts as a barrier in developing treatments. Herein, other routes to develop strategies for understanding calcification mechanism leading toward more advance and effective treatments are studied.